Cytoprotective and antioxidant effects of phenolic compounds from Haberlea rhodopensis Friv. (Gesneriaceae) - Kondeva-Burdina, Magdalena (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Haberlea rhodopensis Friv. (Gesneriaceae) is a rare poikilohydric endemic and preglacial relict growing in Balkan Peninsula. Previous investigations demonstrated strong antioxidant, antimicrobial and antimutagenic potential of alcoholic extract from the plant. OBJECTIVE: The isolation of known caffeoyl phenylethanoid glucoside – myconoside and flavone-C-glycosides hispidulin 8-C-(2-O-syringoyl-β-glucopyranoside), hispidulin 8-C-(6-O-acetyl-2-O-syringoyl-β-glucopyranoside), and hispidulin 8-C-(6-O-acetyl-β-glucopyranoside) from the leaves of H. rhodopensis was carried out. The aim of this study was to investigate cyto-protective and antioxidant effects of isolated compounds. MATERIALS AND METHODS: Antioxidant activity of isolated substances was examined using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radicals; ferric reducing antioxidant power (FRAP) assay and inhibition of lipid peroxidation (LPO) in linoleic acid system by ferric thyocianate method. The compounds were investigated for their possible protective and antioxidant effects against tert-butyl hydroperoxide-induced oxidative stress in isolated rat hepatocytes. The levels of thiobarbituric acid reactive substances were assayed as an index of LPO. Lactate dehydrogenase leakage, cell viability, and reduced glutathione depletion were used as signs of cytotoxicity. RESULTS: Myconoside demonstrated the highest DPPH radical scavenging, ABTS, FRAP, and antioxidant activity in linoleic acid system as well as the highest and statistically most significant protection and antioxidant activity against the toxic agent. CONCLUSION: Phenolic compounds isolated from H. rhodopensis demonstrated significant cytoprotective, radical scavenging potential, and inhibit lipid peroxidation, moreover, myconoside was found to be a new powerful natural antioxidant.